Pengembangan data logger berbasis mikrokontroler untuk praktikum pindah panas - Efendi, Rustam; Tando, Arjal; Herlina (Jurnal Teknik Mesin Indonesia, 2024)
The development of an Arduino Mega 2560-based data logger using the Adafruit AD8495 signal amplifier (connected to a type K thermocouple) is an effort to create an effective and affordable temperature monitoring tool. These sensors are used in various studies involving temperature measurements above and below 0°C. The project aims to design and implement a data logger capable of retrieving temperature data with high accuracy using an Adafruit AD8495 signal amplifier connected to a K-type thermocouple sensor, converting voltage values into readable temperatures, and storing the data in an easy-to-analyze format. This data logger is equipped with the ability to store temperature data on the SD card, allowing monitoring for a longer period of time without having to be continuously connected to a monitoring device. The research method involved the use of Arduino Mega 2560, five pieces of Adafruit AD8495 signal amplifier (connected to type K thermocouple), data logger shield, and other supporting components. The program code is created using the Arduino IDE to operate the temperature data logger. The result of this research is a prototype of a temperature data logger that can be used for various practicum applications and research in the field of temperature, especially in the Mechanical Engineering Laboratory. At an affordable cost, it can provide real-time temperature data with high accuracy, making it a reliable tool for a wide range of purposes. These data loggers have great potential to be used in temperature monitoring in a wide range of applications, from heat transfer research to industrial control.